READINESS OF REGIONAL POLICY MAKERS IN ACCELERATION OF COMMUNITY-BASED TOTAL SANITATION TARGETS - Globila Nurika; Roro Azizah; Setya Haksama; Edza Aria Wikurendra (Universitas Fort De Kock, 2021)
Community-Led Total Sanitation (CLTS) is a sanitation program implemented in Situbondo District, East Java, Indonesia, for nearly ten years. However, Situbondo Regency has not achieved the Indonesian Government's 100% Open Defecation Free (ODF) target. This study aims to analyze policymakers' perspectives in the regions in accelerating CLTS targets' achievement based on a logical model approach. This research is a qualitative observational study with an evaluative method. The design of this research is a case study in Situbondo Regency with informants taken by purposive sampling. The data analysis used is qualitative analysis with the Spradley model. The results of this study indicate that managing stakeholders at the level of program implementers are critical, where program implementers must consider the needs and expectations of program makers to achieve their goals. The impact of policy makers' involvement greatly influences the construction process in producing significant target achievement and the greater influence on a project's success. Also, the achievement and Sustainability of the CLTS program cannot be successful only because of policy makers' readiness of policies. However, the interaction of health workers with the community and the social environment associated with the CLTS program is significant to accelerate its success. The plan's continuation to achieve the target requires policymakers' support and increased interpersonal support for program recipients. Keywords: CLTS; Community-Led Total Sanitation; ODF; Sustainable Program